2015
DOI: 10.5463/dcid.v26i2.412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Physical Disability among Urban Community-dwelling Adults in Sri Lanka

Abstract: Purpose: Assessment of physical disability at the community level is essential for rehabilitation and supply of services. This study aimed to assess the prevalence of physical disability among adults in an urban community in Sri Lanka.Methods: A descriptive cross-sectional study was conducted among 2460 adults (18-59 years of age) who were selected using cluster sampling. Physical disability was measured using a Physical Impairment Examination Tool (PIET) and World Health Organisation Disability Assessment Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A similar pattern was observed in other regional countries. 14,15 Age was found as another risk factor, people 60 years or above found the most vulnerable group for injury related disabilities, this fashion also observed in overall disability prevalence in Bangladesh. 10 Globally, falls, road traffic injury, burn, violence and war are the major causes of injury related disabilities.…”
Section: Discussionmentioning
confidence: 73%
“…A similar pattern was observed in other regional countries. 14,15 Age was found as another risk factor, people 60 years or above found the most vulnerable group for injury related disabilities, this fashion also observed in overall disability prevalence in Bangladesh. 10 Globally, falls, road traffic injury, burn, violence and war are the major causes of injury related disabilities.…”
Section: Discussionmentioning
confidence: 73%
“…"Difficulty seeing" was the commonest domain leading to some degree of functional difficulty. An earlier study in Sri Lanka assessed physical disability among a comparable adult age group and reported a prevalence of 4.2% (95% CI: 3.5-5.1) [30]. Another study from southern India reported a prevalence of 4.7% for mobility-related disability and 2.1% for vision-related severe grades of disability [31].…”
Section: Original Articlementioning
confidence: 99%